PELAKSANAAN PEMBAGIAN HARTA BERSAMA AKIBAT PUTUSNYA PERKAWINAN KARENA PERCERAIAN PASCA PUTUSAN MAHKAMAH KONSTITUSI NOMOR 64/PUU-X/2012 TENTANG KERAHASIAAN BANK (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The implementation of the sharing of shared assets can be carried out in court. The court in question is the District Court and the Religious Court / Sharia Court. On religious courts / Syariah Court, distribution of shared assets can be carried out simultaneously with the divorce and can also be separated by divorce, while in the District Court, the sharing of shared assets must be separated by divorce. In this study, the author wants to examine the implementation of the sharing of shared assets in the form of money and assets saved by one of the parties in the bank after the issuance of the Constitutional Court Decision Number 64 / PUU-X / 2012 which is testing article 40 of the banking law concerning bank secrets , the decision of the Constitutional Court is intended to protect the rights of the husband / wife to the joint assets saved by one of the parties in the bank , because the joint assets are assets acquired by the husband and wife after the marriage, so that the husband and wife are entitled to the joint property, so that in its decision the Constitutional Court added the exception to the opening of bank secrets, namely that bank secrets could be opened to resolve the problem of sharing property together in the divorce case.The purpose of this thesis is: First to find out the implementation of the sharing of joint assets due to the termination of the marriage due to divorce when the Constitutional Court Decision Number 64 / PUU-X / 2012 concerning bank secrecy. Secondly, to find out the ideal arrangement for the distribution of joint property of marriage that is registered in the bank in order to realize legal certainty regarding the rights of husband / wife in divorce cases .This type of research is normative legal research or also called doctrinal legal research and this research is descriptive. The data sources used in this study are secondary data, namely data obtained from the literature such as legal journals, books, judge decisions relating to research. This data analysis is carried out qualitatively and deductively withdrawn.From the results of this study there are two main problems that can be concluded, First, that after the decision of the Constitutional Court was issued, husbands and wives have been able to open customer and deposit dataprotected by bank secrets in divorce cases. Second, see in the Decision of the Constitutional Court that it does not specifically explain whether the a quo ruling also has binding legal force on the case of the sharing of shared assets separated by divorce cases, so as not to give legal certainty to the division of joint property separated by divorce, so according to the author there must be a renewal of the Banking Law and Bank Indonesia Regulations on Constitutional Court Decisions and are also confirmed to apply to the distribution of shared assets separated by divorce.Keywords: Marriage, Shared Assets, Bank Secrets